Scalability and homogeneity of slot die‐coated metal oxide semiconductor for TFTs. Issue 6 (21st May 2016) - Takata, Ryo; Neumann, Anita; Weber, Dennis; Pham, Duy‐Vu; Anselmann, Ralf; Kitamura, Yoshitaka; Kakimura, Takashi; Suzuki, Satoshi; Minami, Shigeki; Kodama, Mitsumasa
Abstract : An indium oxide‐based precursor solution has been developed by spin coating method. In order to apply this material to mass production, material, process, and equipment optimizations for slot die coating have been implemented. Slot die coating is a cost‐effective and scalable process and already applied to photoresist materials in the display industry. The indium oxide‐based precursor solution has been coated on bare glasses and thin‐film transistor substrates by a mass production‐type slot die coater. Mobility of over 10 cm 2 /Vs is achieved for the first time for a large area at an annealing temperature of 350 °C. The homogeneity of the film will be presented. Abstract : An indium oxide‐based precursor solution has been coated on bare glasses and thin‐film transistor substrates by a mass production‐type slot die coater. Mobility of over 10 cm 2 /Vs is achieved for the first time for a large area at an annealing temperature of 350 °C. The homogeneity of the film will be presented.